2021
DOI: 10.1002/anie.202101104
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Cyclohepta[b]indoles by Visible‐Light‐Induced [2+2]‐Cycloaddition/retro‐Mannich‐type Reactions

Abstract: A novel method for the concise synthesis of cyclohepta [b]indoles in high yields was developed. The method involves a visible-light-induced, photocatalyzed [2+2]-cycloaddition/ retro-Mannich-type reaction of enaminones. Experimental and computational studies suggested that the reaction is a photoredox process initiated by single-electron oxidation of an enaminone moiety, which undergoes subsequent cyclobutane formation and rapidly fragmentation in a radical-cation state to form cyclohepta[b]indoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…23–27 In addition, the Michael addition reaction is also efficient in the synthesis of many important pharmaceutical intermediates and natural products. 28–30 This type of reaction has the advantages of mild conditions, easily accessible starting materials, and a wide range of applications. 31,32 In the last few years, many catalysts such as InCl 3 , 33 TiCl 4 , 34 and metal catalysts 25 have been reported in the Michael addition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…23–27 In addition, the Michael addition reaction is also efficient in the synthesis of many important pharmaceutical intermediates and natural products. 28–30 This type of reaction has the advantages of mild conditions, easily accessible starting materials, and a wide range of applications. 31,32 In the last few years, many catalysts such as InCl 3 , 33 TiCl 4 , 34 and metal catalysts 25 have been reported in the Michael addition reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Five-membered enaminones are widely used as attractive building blocks for the synthesis of structurally diverse heterocycles. 11–24 For example, Liu et al reported the synthesis of N -fused polycyclic and 2,3-disubstituted indoles by the copper-catalyzed direct annulation/acyl migration reaction of cyclic enaminones. 11 In turn, Troin and coworkers showed an efficient route to indole alkaloid synthons via the photochemical cyclization of aryl enaminones.…”
mentioning
confidence: 99%
“…The product or intermediate obtained by the ring-opening process can be further employed in subsequent transformations to acquire more complex and valuable structures. Therefore, [2 + 2]-photocycloaddition and its subsequent ring-opening reaction are expected to be important steps in pericyclic cascade reactions . Numerous cascade reactions consisting of [2 + 2]-photocycloaddition and ring-opening have been reported.…”
mentioning
confidence: 99%